La determinación de la pena en la práctica judicial chilena = Sentencing in Chilean courts - Wilenmann, Javier (Política criminal, 2019)
By using available and complementary data produced for this study, the paper reconstructs recurring practices of sentencing in the Chilean criminal justice system. How are concrete sentences established by Chilean courts? Under which conditions is parole granted? When do Chilean courts deviate from the more general standards of judicial behavior? The paper attempts to establish recurring behavior in Chilean criminal courts, in order to assess its effects in the criminal justice and corrections system and to evaluate the merits and shortcomings of the local reality of sentencing.